Pengembangan Kompetensi Sumber Daya Manusia Sebagai Kunci Inovasi Dan Transformasi UMKM Batik Di Era Globalisasi - Junengsih; Basori, Mohamat; Intan, Lusi Reni; Triana, Ade (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study explores the role of human resource (HR) competencies in driving innovation and transformation in batik SMEs, amidst globalization challenges. A qualitative descriptive method was employed to collect data through observation, interviews, and surveys. The findings reveal that most batik SMEs possess basic competencies in batik production but require improvements in design innovation and technology adaptation. Developing HR competencies through digital design training, online marketing, and strategic management is essential to enhance competitiveness and business sustainability. This study recommends continuous training programs and cross-sector collaborations to support the growth of batik SMEs in domestic and international markets.